2022
DOI: 10.1101/2022.02.20.481240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An Ethogram Identifies Behavioural Markers of Attention to Humans in European Herring Gulls (Larus argentatus)

Abstract: Herring gulls are one of the few species that thrive in anthropogenic landscapes. Their longstanding history of urbanisation and familiarity with people makes them an excellent target for studies of the effects of urban living and cognition. Previous studies highlight a connection between food-stealing behaviour, success in anthropogenic areas and an increase in attention towards humans, opening up questions about the exact extent of a gull's knowledge of human food cues and how this manifests itself in behavi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 36 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…Previous work [ 24 ] has shown that group size does not influence the frequency of attentional markers; thus, single individual herring gulls and groups of less than five were approached after assessing the area to ensure there were no dogs or pedestrians moving in the immediate vicinity. The presented stimuli were two Walkers brand crisp packets, one blue, one green, taped to 15 cm × 20 cm ceramic tiles, which were laid out 1.5 m apart and 5–10 m away from the gulls.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work [ 24 ] has shown that group size does not influence the frequency of attentional markers; thus, single individual herring gulls and groups of less than five were approached after assessing the area to ensure there were no dogs or pedestrians moving in the immediate vicinity. The presented stimuli were two Walkers brand crisp packets, one blue, one green, taped to 15 cm × 20 cm ceramic tiles, which were laid out 1.5 m apart and 5–10 m away from the gulls.…”
Section: Methodsmentioning
confidence: 99%
“…Recordings were uploaded into the Behavioural Observation Research Interactive Software (BORIS) [ 31 ] and a log of head turn counts was created, while approaches and pecks were noted as ‘yes’ or ‘no’ along with whether they colour-matched the experimenter's item during PC trials. These behaviours were chosen based on previous work showing that they are upregulated when a demonstrator is consuming food rather than simply mimicking feeding actions [ 24 ]. For an individual to be included in the analysis it had to be present in the video for 30 s or more or peck at one of the provided crisp packets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data was collected during daylight hours (7:00-16:00) along the Brighton beachfront, UK (50.8193° N, 0.1364° W), from May-June 2021 and March-May 2022. Differing weather conditions only affected gull presence but not behaviour (Feist and Graham, 2022), however low tide periods were avoided as gulls engage more in natural foraging and were consequently less likely to engage with the experiment. Furthermore, data was only collected on weekdays to minimise pedestrian disturbance.…”
Section: Study Sitementioning
confidence: 99%
“…Interestingly, in urban populations there is evidence that herring gulls have also learned to obtain foraging information from humans. Recent studies have found gulls are able to adapt their foraging behaviour to human activity patterns (Spelt et al, 2021), increase their attention towards a person in possession of food (Feist and Graham, 2022), and pay attention to behavioural cues such as gaze (Goumas et al, 2019; Goumas et al, 2020b) and to which items have been handled (Kelley, Boogert and Goumas, 2020a). This shows that gull populations have the cognitive and behavioural flexibility to adapt foraging behaviour to human cues.…”
Section: Introductionmentioning
confidence: 99%